Computer Human Interaction: A Blessing or Curse for Ghanaian Youth? - Adam Andani, Mohammed; Adibah, Yusuf; Mpawenimana, Abdallah Saidi (Human Resource Management Academic Research Society, 2019)
Information and Communication Technology ICT and Traditional African Religion TAR (Voodoo/Vodou) promote the integration of socio-cultural, political and economic system of the people in Africa. However, the youth, (Sakawa Boys) merge technology with religion to commit internet fraud. Sakawa is the use of evil occult powers to commit internet fraud by possessing the mind of the foreign cyber target. These Sakawa boys manipulate vodou powers by performing certain frightening rituals for spiritual empowerment before logging into the internet. This has brought different changes to the socio-cultural and ideological bases of Ghanaians. This study reviewed literature on the causal factors, their modus operandi and the consequences of technology human interaction in Ghana. The Internet and Vodou rituals are found to be the major driving force for Sakawa boys to practice their trade. The consequences of the activities of these boys included infertility, mental illness, sickness or death for the perpetrators and the victims of their ritual sacrifices. Based on traditional ethos, this has transformed the preferences and social values of the youth in Ghana.